A genetic switch for worker nutrition-mediated traits in honeybees - Annika Roth; Christina Vleurinck; Oksana Netschitailo; Vivien Bauer; Marianne Otte; Osman Kaftanoğlu; Robert E. Page; Martin Beye (2019)
Highly social insects are characterized by caste dimorphism, with distinct size differences of reproductive organs between fertile queens and the more or less sterile workers. An abundance of nutrition or instruction via diet-specific compounds has been proposed as explanations for the nutrition-driven queen and worker polyphenism. Here, we further explored these models in the honeybee (Apis mellifera) using worker nutrition rearing and a novel mutational screening approach using the clustered regularly interspaced short palindromic repeats/CRISPR-associated protein 9 (CRISPR/Cas9) method. The worker nutrition-driven size reduction of reproductive organs was restricted to the female sex, suggesting input from the sex determination pathway. Genetic screens on the sex determination genes in genetic females for size polyphenism revealed that doublesex (dsx) mutants display size-reduced reproductive organs irrespective of the sexual morphology of the organ tissue. In contrast, feminizer (fem) mutants lost the response to worker nutrition-driven size control. The first morphological worker mutants in honeybees demonstrate that the response to nutrition relies on a genetic program that is switched "ON" by the fem gene. Thus, the genetic instruction provided by the fem gene provides an entry point to genetically dissect the underlying processes that implement the size polyphenism.